Rekonstruksi Etika Komunikasi Islam Berbasis Teoantropoekosentris - Arif Aminin; Juni Wati Sri Rizki (IAIN Padangsidimpuan, 2026)
The rapid development of global and digital communication has generated increasingly complex ethical challenges for Islamic communication, particularly as religious communication practices remain largely normative, anthropocentric, and insufficiently responsive to the global ecological crisis. This condition highlights the urgency of reconstructing Islamic communication ethics that integrate theological, humanistic, and ecological dimensions in a comprehensive manner. This study aims to reconstruct Islamic communication ethics based on a theo-anthropo-ecocentric paradigm as an effort to address the limitations of conventional Islamic communication ethics. Employing a qualitative approach through library research, this study conducts critical analysis and conceptual synthesis of reputable academic literature, normative Islamic sources, as well as studies on communication ethics and environmental ethics. The findings indicate that the theo-anthropo-ecocentric paradigm expands the framework of Islamic communication ethics by positioning God as the source of values, humans as moral subjects and responsible communicators, and nature as a valuable entity that must be preserved through just and sustainable communication practices. This reconstruction results in a holistic, contextual, and contemporary model of Islamic communication ethics, particularly relevant to da‘wah and public communication. The study underscores that integrating theological, anthropological, and ecological dimensions into Islamic communication ethics constitutes a significant contribution to the development of Islamic communication studies and the practice of ethical religious communication.Keywords: Islamic Communication Ethics, Theo-Anthropo-Ecocentrism